State-dependent monetary policy transmission and financial market tensions - Rüth, Sebastian (Economics letters, 2017)
Is monetary policy more powerful when strains in the financial system are high? Applying local projections to US time series, I approach this question by allowing monetary policy shocks and its propagation to the broader economy to smoothly vary according to a measure of financial market tensions—the so-called excess bond premium (EBP). I find that monetary policy impacts macroeconomic, housing, and financial variables stronger and more persistently when financial frictions are high.